Genome-Wide Association Mapping of Seedling Heat Tolerance in Winter Wheat - Maulana, Frank; Ayalew, Habtamu; Anderson, Joshua D.; Kumssa, Tadele T.; Huang, Wangqi; Ma, Xue-Feng (Frontiers in Plant Science, 2018)
Heat stress during the seedling stage of early-planted winter wheat (Triticum aestivum L.) is one of the most abiotic stresses of the crop restricting forage and grain production in the southern Plains of the United States. To map quantitative trait loci (QTLs) and identify single nucleotide polymorphism (SNP) markers associated with seedling heat tolerance, a genome-wide association mapping study (GWAS) was conducted using 200 diverse representative lines of the hard red winter wheat association mapping panel, which was established by the Triticeae Coordinated Agricultural Project (TCAP) and genotyped with the wheat iSelect 90K SNP array. The plants were initially planted under optimal temperature conditions in two growth chambers. At the three-leaf stage, one chamber was set to 40/35ºC day/night as heat stress treatment, while the other chamber was kept at optimal temperature (25/20ºC day/night) as control for 14 days. Data were collected on leaf chlorophyll content, shoot length, number of leaves per seedling, and seedling recovery after removal of heat stress treatment. Phenotypic variability for seedling heat tolerance among wheat lines was observed in this study. Using the mixed linear model (MLM), we detected multiple significant QTLs for seedling heat tolerance on different chromosomes. Some of the QTLs were detected on chromosomes that were previously reported to harbor QTLs for heat tolerance during the flowering stage of wheat. These results suggest that some heat tolerance QTLs are effective from the seedling to reproductive stages in wheat. However, new QTLs that have never been reported at the reproductive stage were found responding to seedling heat stress in the present study. Candidate gene analysis revealed high sequence similarities of some significant loci with candidate genes involved in plant stress responses including heat, drought and salt stress. This study provides valuable information about the genetic basis of seedling heat tolerance in wheat. To the best of our knowledge, this is the first GWAS to map QTLs associated with seedling heat tolerance targeting early planting of dual-purpose winter wheat. The SNP markers identified in this study will be used for marker-assisted selection of seedling heat tolerance during dual-purpose wheat breeding.